2012
DOI: 10.1111/j.1365-2427.2012.02767.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of large wood on brown trout (Salmo trutta) behaviour and surface foraging

Abstract: Summary 1. Changes in riparian vegetation owing to forest harvesting may affect the input of large wood, a major structural element, to streams. Studies of large wood impacts on stream fish have focused on population‐level responses, whereas little attention has been given to how wood affects fish behaviour. 2. In a laboratory stream experiment, we tested how two size classes of brown trout, Salmo trutta, (mean size of 85 and 125 mm), alone and together, responded to a gradient of large wood in terms of activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 72 publications
5
15
5
Order By: Relevance
“…Our study showed a 67% decrease in cruising time when FW was introduced, which is similar to the 74% decrease in activity reported by Gustafsson et al. () for single small trout in habitats with added large wood (LW). Also, total average trout activity in our study (21.7% of time) was similar to the 27.7% activity of small trout in the study with LW.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study showed a 67% decrease in cruising time when FW was introduced, which is similar to the 74% decrease in activity reported by Gustafsson et al. () for single small trout in habitats with added large wood (LW). Also, total average trout activity in our study (21.7% of time) was similar to the 27.7% activity of small trout in the study with LW.…”
Section: Discussionsupporting
confidence: 91%
“…; Gustafsson et al. ; but see Fenderson & Carpenter ). Growth and mortality rates of juvenile brown trout in streams are density dependent (Lobón‐Cerviá ; Vøllestad & Moland Olsen ), and the density dependence can be more pronounced for small than large fish (Jenkins et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Fourth, high wood densities increase visual isolation between competitors and thereby probably decrease interactions between conspecifics (Kalleberg, 1958;Imre et al, 2002;, presumably decreasing energy expenditure and enhancing growth. Gustafsson et al (2012) found that aggressive interactions were substantially reduced at wood densities similar to those used in the present study, and moreover, the ratio of the proportion of successful prey captures to time spent actively swimming increased by approximately 350% with increasing wood densities. Thus, the addition of wood has most likely influenced growth in several ways, not only providing the fish with greater prey resources, but also by influencing foraging behaviour and levels of aggression.…”
Section: Discussionsupporting
confidence: 71%
“…; Gustafsson et al . ). The mechanisms behind this are probably reduced visual contact among dominant individuals and increased cost of territory defence (Eason and Stamps ; Dolinsek et al .…”
Section: Ecological Relevance Of Structural Complexitymentioning
confidence: 97%